Isolated incomplete cryptophthalmos with bilateral non-syndromic microphthalmia – a rare clinical entity - Trifonova, Kalina; Slaveykov, Kiril (Klinika Oczna / Acta Ophthalmologica Polonica, 2026)
We report a case of a full-term newborn Caucasian girl presenting at 10 days of age with bilateral absence of upper eyelid creases, extremely short palpebral fissures, and mucosal tissue covering both globes. B-scan ultrasonography and magnetic resonance imaging revealed bilateral microphthalmia, more pronounced in the left eye, with hypoplastic optic nerves. No other systemic anomalies were detected. The patient demonstrated normal psychomotor development and responded to light stimuli at ten months. Differential diagnoses included anophthalmia, blepharophimosis, and microblepharon; however, clinical and imaging findings supported a diagnosis of incomplete bilateral cryptophthalmos. Given the poor visual prognosis, surgical intervention was deferred, with plans for future reconstructive consideration. This case underscores the diagnostic challenges of cryptophthalmos, the limitations of prenatal imaging, and the need for a multidisciplinary approach involving ophthalmology, radiology, genetics, and reconstructive surgery in managing complex congenital ocular anomalies.